Mathematics and reality - Leng, Mary. (Oxford : Oxford University Press, 2010)
Mary Leng defends a philosophical account of the nature of mathematics which views it as a kind of fiction (albeit an extremely useful fiction).
Description based on print version record.
Includes bibliographical references and index.
Keywords: Mathematics -- Philosophy